ChemInform Abstract: General Synthetic Approach Towards Anellated 3a, 6‐Epoxyisoindoles by Tandem Acylation/IMDAF Reaction of Furylazaheterocycles. Scope and Limitations. Issue 31 (5th August 2014) - Zubkov, Fedor I.; Nikitina, Eugenia V.; Galeev, Timur R.; Zaytsev, Vladimir P.; Khrustalev, Victor N.; Novikov, Roman A.; Orlova, Daria N.; Varlamov, Alexey V.
Abstract The method is based on the condensation of preformed or in situ generated α‐furyl substituted azaheterocycles with acryloyl chloride or maleic anhydride via N‐acylation and intramolecular Diels—Alder reaction of the furan moiety.